2017
DOI: 10.1016/j.carres.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Infant food applications of complex carbohydrates: Structure, synthesis, and function

Abstract: Professional health bodies such as the World Health Organization (WHO), the American Academy of Pediatrics (AAP), and the U.S. Department of Health and Human Services (HHS) recommend breast milk as the sole source of food during the first year of life. This position recognizes human milk as being uniquely suited for infant nutrition. Nonetheless, most neonates in the West are fed alternatives by 6 months of age. Although inferior to human milk in most aspects, infant formulas are able to promote effective grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 187 publications
(193 reference statements)
1
50
0
Order By: Relevance
“…However, critical bioactive components found in human breast milk may be lacking in infant formula, and to address this, the composition of infant formula has changed over time (Lonnerdal 2014). Present-day infant formula is now supplemented with components such as oils, starches, and vitamins to better align with human milk (Ackerman et al 2017). However, human milk contains an array of diverse bioactive structures, and the production of structurally and compositionally similar molecules remains a challenging task.…”
Section: Diets Supplemented With Exogenous Milk Oligosaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, critical bioactive components found in human breast milk may be lacking in infant formula, and to address this, the composition of infant formula has changed over time (Lonnerdal 2014). Present-day infant formula is now supplemented with components such as oils, starches, and vitamins to better align with human milk (Ackerman et al 2017). However, human milk contains an array of diverse bioactive structures, and the production of structurally and compositionally similar molecules remains a challenging task.…”
Section: Diets Supplemented With Exogenous Milk Oligosaccharidesmentioning
confidence: 99%
“…Because HMOs are not readily available as an ingredient, infant formulas are now commonly supplemented with inulin and galactooligosaccharides (GOSs) or fructooligosaccharides (FOSs) (Ackerman et al 2017), and these commercial prebiotics have been shown to increase bifidobacterial abundance in vivo (Haarman & Knol 2005, Knol et al 2005, Ramirez-Farias et al 2009). Although these carbohydrates are prebiotic, emerging research is showing that they do not possess other important bioactivities of milk oligosaccharides.…”
Section: Diets Supplemented With Exogenous Milk Oligosaccharidesmentioning
confidence: 99%
“…Glycosyl linkages include b1,3, b1,4 and/or b1,6. The type of linkage is determined by the enzyme source used to link the different units (Ackerman et al 2017;Intanon et al 2014). Like HMOs, GOS can reach the large intestine, where they can act as prebiotics (Macfarlane et al 2008).…”
Section: Galacto-oligosaccharidesmentioning
confidence: 99%
“…The length of the chain typically ranges from 2 to 10 units with variations in branching and glycosyl linkage (Ackerman et al 2017). Glycosyl linkages include b1,3, b1,4 and/or b1,6.…”
Section: Galacto-oligosaccharidesmentioning
confidence: 99%
“…Since E.coli is the most common system used, and there is much and good information about the mutants with no virulent capacity, the downstream production requires controls that guarantee endotoxin-free production (Sprenger, Baumgärtner, & Albermann, 2017) NDCs should not be abandoned. Many of the carbohydrates used to fortify infant formula have been extensively investigated as food ingredient for their prebiotic properties (Ackerman, Craft, &Townsend, 2017). Unfortunately, it has not been fully confirmed that they can substitute for other relevant functions of HMOs (Kent, 2006).…”
Section: Host Genetic Factorsmentioning
confidence: 99%